Re-territorialising the policing of cybercrime in the post-COVID-19 era: towards a new vision of local democratic cyber policing. Issue 3 (18th January 2021) - Horgan, Shane; Collier, Ben; Jones, Richard; Shepherd, Lynsay
Abstract : Purpose: The purpose of this study is to develop the theorisation of cybercrime in the context of the pandemic, and to sketch out a vision of how law enforcement might respond to a transformed landscape of online crime and offending. Design/methodology/approach: This conceptual paper draws on empirical evidence from a range of sources (including official statistics) and the existing research literature, and revisits routine activities theory to illuminate the way that cybercrime patterns are being transformed by the pandemic. Findings: The pandemic is reshaping the routine activities of societies en masse, leading to changes in the ecology of risk and opportunity for cybercrime. There is evidence of a large increase in the prevalence of cybercrime as a result, yet much of this has a paradoxically "local" character. Practical implications: The authors identify specific practical implications for law enforcement, namely, that the role of local police in policing cybercrime should be re-envisioned, with a democratic, community-oriented approach at its heart. Originality/value: The theoretical perspective outlined is a novel and critical development of a well-established framework, opening up new paths to the theorisation of cybercrime and cybercrime policing. The authors' suggestions for practitioners have the potential for direct impact, both at the level of practice and in terms of broader imaginaries and organisation of police and policing.